Alteration of Serum levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), C-reactive protein (CRP), gastrin (GAS) and motilin (MTL) after treatment in the Helicobacter pylori-positive gastric ulcer: Serum levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), C-reactive protein (CRP), gastrin (GAS) and motilin (MTL) - Chu, Yunxiang; Jin, Lin; Weng, Yan; Liu, Xiaochuan (Journal of Medical Biochemistry, 2025)
Aim:This study aimed to explore the clinical efficacy of probiotics plus quadruple therapy on Serum levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), C-reactive protein (CRP), gastrin (GAS) and motilin (MTL)  in treating Helicobacter pylori (Hp)-positive gastric ulcer (GU).Methods:One hundred and twenty-four patients with Hp-positive GU treated in our hospital from January 2021 to January 2024 were randomly separated into control group and observation group. The former received conventional quadruple therapy, and the latter received tetralogy of viable bifidobacterium tablets combined with conventional quadruple therapy. The clinical efficacy, Hp eradication rate, levels of inflammatory cytokines and gastrointestinal hormone, incidence of adverse reactions along with quality of life were compared in 2 groups. Results:The total effective rate of the observation group was 96.77%, higher than that of the control group (82.25%). The Hp eradication rate in the observation group was higher than the control group. After therapy, IL-6, TNF-α and CRP levels were declined in 2 groups, and those in the observation group presented lower as comparing with the control group. After therapy, MLT level was elevated while GAS level was declined in 2 groups, and the improvements of MLT and GAS levels in the observation group were more significant as comparing with the control group. The incidence of diarrhea in the observation group was lower than that in the control group, and there was no difference in the incidence of nausea and abdominal distension between 2 groups. Conclusion:After therapy, physiological function, physical function, emotional function, body pain, general health, mental health, vitality and social function scores were elevated in 2 groups, and those in the observation group presented higher as comparing with the control group. Probiotics combined with quadruple therapy is effective and safe in the treatment of Hp-positive GU, which can promote the Hp eradication rate, improve the inflammation response and gastrointestinal hormone levels, maintain the balance of intestinal flora and promote the quality of life of patients.
Keywords: Serum levels of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), C-reactive protein (CRP), gastrin (GAS) and motilin (MTL) ,Helicobacter pylori, Gastric ulcer, Probiotics, Quadruple therapy, Inflammation, Intestinal flora